Does environmental regulatory system drive the green development of China's pollution-intensive industries?. (1st January 2022) - Zou, Han; Zhang, Yijun
Abstract: Green development is a common goal pursued globally for carbon neutrality, and whether environmental regulatory system drives it in pollution-intensive industries (PIIs) is puzzled. Using provincial panel data of Chinese PIIs during 2005–2017, this paper applied entropy method to integrate existing environmental regulatory system into three types of environmental regulations, and then explored non-linear effects of them on green total factor productivity (GTFP). Several conclusions are generated. The annual growth rate of GTFP is 10.61% and it presents industrial differences. Technical change is the driving factor, while technical efficiency shows inhibiting effect. The effect of command-and-control environmental regulation on GTFP is a significant inverted U-shape curve, which is currently the primary driving role in green development, but it is too strict and increasingly less effective. Both market incentive and voluntary environmental regulations appear as positive U-shape curves, and their proper enhancement is breakthrough for future green development. Besides, market incentive environmental regulation is more effective in PIIs with relatively low pollution, while voluntary environmental regulation is sensitive to PIIs with relatively serious pollution. The Chinese government should allow environmental regulatory system more marketability and voluntariness, and production characteristics and pollution density of targeted industries should be considered. Highlights: The green development grows rapidly but shows technical inefficiency. Command-and-control environmental regulation drives green development effectively. Market incentive and voluntary environmental regulations can be enhanced properly. Market incentive environmental regulation is sensitive to slight-polluted industries. Voluntary environmental regulation works in heavy-polluted industries.